ChemInform Abstract: LiBC —Synthesis, Electrochemical and Solid‐State NMR Investigations. Issue 9 (5th March 2013) - Langer, Thorsten; Dupke, Sven; Dippel, Christian; Winter, Martin; Eckert, Hellmut; Poettgen, Rainer
Abstract LiBC is synthesized from the elements (Nb ampule, 700 mbar Ar, 1800 K for 15 min, 1000 K for 2 h) and characterized by powder and single crystal XRD and 6/7Li and 11B solid state NMR spectroscopy.